2020
DOI: 10.24294/jipd.v4i2.1206
|View full text |Cite
|
Sign up to set email alerts
|

The impact of infrastructure investment on economic growth in the United Kingdom

Abstract: Infrastructure investment has long been held as an accelerator or a driver of the economy. Internationally, the UK ranks poorly with the performance of infrastructure and ranks in the lower percentile for both infrastructure investment and GDP growth rate amongst comparative nations. Faced with the uncertainty of Brexit and the likely negative economic impact this will bring, infrastructure investment may be used to strengthen the UK economy. This study aims to examine how infrastructure funding impacts econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…These ripple effects were as a result of changing patterns on consumption (Jara-Díaz, 2007;Wang et al, 2012), production (Lakshmanan, 2011;Oosterhaven and Knaap, 2003;Rodrigue, 2020), and transport substitutions (Cats et al, 2017;Kwok and Yeh, 2004). This hypothesis aligned with the broader academic literature, which posited that robust investments in transport infrastructure can yield far-reaching economic benefits (Berechman, 2001;Seidu et al, 2020). Furthermore, it underlined the pragmatic policy implications of sustained and strategic investments in transport infrastructure as a means to foster economic resilience and growth, a perspective echoed in the development policies of various nations (Kemmerling and Stephan, 2002;Lee, 2021).…”
Section: Discussionmentioning
confidence: 53%
“…These ripple effects were as a result of changing patterns on consumption (Jara-Díaz, 2007;Wang et al, 2012), production (Lakshmanan, 2011;Oosterhaven and Knaap, 2003;Rodrigue, 2020), and transport substitutions (Cats et al, 2017;Kwok and Yeh, 2004). This hypothesis aligned with the broader academic literature, which posited that robust investments in transport infrastructure can yield far-reaching economic benefits (Berechman, 2001;Seidu et al, 2020). Furthermore, it underlined the pragmatic policy implications of sustained and strategic investments in transport infrastructure as a means to foster economic resilience and growth, a perspective echoed in the development policies of various nations (Kemmerling and Stephan, 2002;Lee, 2021).…”
Section: Discussionmentioning
confidence: 53%
“…Despite evidence that infrastructure investments may divert economic activity (Gibbons et al, 2019;Haughwout, 1999;Wachs, 2011), the economic performance effects of these investments are overwhelmingly positive. Studies have shown that the UK (Young et al, 2020), Netherlands (Sturm et al, 1999), Central and Eastern European countries (Chi, 2015;Vlahinić Lenz et al, 2018), Belgium (Meersman and Nazemzadeh, 2017), India (Mohanty et al, 2022;Rudra Pradhan and Bagchi, 2013), China (Chen, 2019;Ren and Ding, 2019), Japan (Yoshino and Abidhadjaev, 2017), and Asia (Sawada, 2019) all exhibit positive economic performance effects. Three key takeaways from this literature are that overall economic performance effects tell us nothing about their constituent parts; we need to look under the aggregate hood and examine industryspecific effects as we do in this study, much like the construction of transportation infrastructure creates jobs, so does its maintenance; and finally, the full economic impact may not be known until years after a project is completed, making a dynamic long-run analysis of these effects paramount for a comprehensive appraisal.…”
Section: Transportation Infrastructurementioning
confidence: 99%
“…[9,7,1] many studies in literature examine the relationship between FDI and economic growth. Similarly, for transportation [10][11][12]. The researchers have used different econometric techniques to test the relationship between economic growth and its other drivers.…”
Section: Literature Reviewmentioning
confidence: 99%